IMAM AL-BUKHARI - A GREAT SCIENTIST (Scientific journal of the Fergana State University, 2024)
This article focuses on the life path and scientific activity of Imam al-Bukhari, one of the brightest representatives of the renaissance process, one of the great representatives of religion, which took place in the Movarounnahr region in the 9th-12th centuries. The main purpose of the study is to further study the exemplary life and effective activity of Imam Bukhari and popularize it among readers. In addition, as a descendant of great people like Imam al-Bukhari, it is right to say that researching their activities and taking a creative approach should be the duty of every researcher today. In studying and researching the life path and activities of Imam al-Bukhari, we rely on specific facts presented by historians, information from literary scholars, religious scholars and hadith scholars, and information given by representatives of several fields based on their field. It is the right way to compare, analyze and summarize data. Inconsistencies are noticeable in some figures given by representatives of various fields of science about Bukhari's life and work. Such a situation creates inconvenience for readers and people interested in Bukhari's life. This article will focus on these disparities.